Online economic calculator for crop treatments applications-Africa version- - Abbate, Pablo Eduardo; Edwards Molina, Juan Pablo; Bronzovich, Nicolás (Estación Experimental Agropecuaria Balcarce, INTA., 2022)
The web page presented was developed within the framework of the agreement between INTA Balcarce (National Institute of Agricultural Technology, Agricultural Experimental Station Balcarce; Buenos Aires, Argentina; https://inta.gob.ar/balcarce) and the International Program of AAPRESID (Argentine Association of Direct Sowing Producers, Argentina; https://www.aapresid.org.ar), with the intention of promoting conservation agriculture among African producers. The page is based on a page previously developed by J.P. Edwards Molina and P.E. Abbate (https://cultivaresargentinos.com/proteccion) aimed at evaluating treatments in grain crops of Argentine producers.